1993
DOI: 10.1073/pnas.90.3.938
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a constitutively active erythropoietin receptor in primary hematopoietic progenitors abrogates erythropoietin dependence and enhances erythroid colony-forming unit, erythroid burst-forming unit, and granulocyte/macrophage progenitor growth.

Abstract: We tested the ability of a constitutively activated erythropoietin receptor [EpoR(R129C)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Previous studies have shown that dimerization of the EPOR stimulates the signals leading to erythroid cell survival, proliferation, and differentiation (8,10,11,44). Crystallographic structural analysis of the EPOR extracellular region complexed to a peptide agonist demonstrated directly the dimeric nature of the receptor, and biochemical experiments have shown that EPO promotes dimerization of the EPOR extracellular region (9,12,52).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dimerization of the EPOR stimulates the signals leading to erythroid cell survival, proliferation, and differentiation (8,10,11,44). Crystallographic structural analysis of the EPOR extracellular region complexed to a peptide agonist demonstrated directly the dimeric nature of the receptor, and biochemical experiments have shown that EPO promotes dimerization of the EPOR extracellular region (9,12,52).…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting inductive, or instructive, hypothesis attributes to growth factors a direct role in cell differentiation, predicting that growth factor receptors transduce signals that uniquely specify the differentiation outcome of a progenitor (15)(16)(17). A number of hybrid hypotheses have also been proposed, where, for example, committed progenitors arise stochastically, but their subsequent differentiation and acquisition of the mature phenotype are uniquely induced by lineage-specific growth factors (18).Although Epo is essential for the production of red blood cells, it is not thought to play a role in the generation of committed erythroid progenitors from pluripotent progenitors: expression of recombinant EpoR does not bias the lineage commitment of pluripotent hematopoietic progenitors (19,20), and normal numbers of committed erythroid BFU-e and CFU-e progenitors are found in the fetal livers of EpoR Ϫ/Ϫ mutant mice (21). However, there is a unique requirement for EpoR activation during the subsequent proliferation and terminal differentiation of committed erythroid progenitors: the EpoR Ϫ/Ϫ CFU-e and BFU-e progenitors fail to give rise to mature erythrocytes unless EpoR is expressed by retroviral infection (21); and in vitro, other growth factors only partially substitute for .…”
mentioning
confidence: 99%
“…Although Epo is essential for the production of red blood cells, it is not thought to play a role in the generation of committed erythroid progenitors from pluripotent progenitors: expression of recombinant EpoR does not bias the lineage commitment of pluripotent hematopoietic progenitors (19,20), and normal numbers of committed erythroid BFU-e and CFU-e progenitors are found in the fetal livers of EpoR Ϫ/Ϫ mutant mice (21). However, there is a unique requirement for EpoR activation during the subsequent proliferation and terminal differentiation of committed erythroid progenitors: the EpoR Ϫ/Ϫ CFU-e and BFU-e progenitors fail to give rise to mature erythrocytes unless EpoR is expressed by retroviral infection (21); and in vitro, other growth factors only partially substitute for .…”
mentioning
confidence: 99%
“…(21) R129C also supports Epo-independent erythropoiesis in ex vivo cultures. (25) Collectively, these results demonstrate that R129C signaling is dominant to the endogenous WT EpoR. Therefore, use of R129C-containing EpoR mutants is a powerful method to analyze EpoR signaling requirements in a wild-type genetic background.…”
Section: Fetal Liver Cfu-e Development Is Supported By Epors That Actmentioning
confidence: 95%
“…This approach has been used previously to study EpoR functions, as it enables rapid analysis of receptor mutants in primary erythroid cells. (16,21,22,25,26) ER343-S3, ER401-S3, and ER343/401-S3 support CFU-E development from fetal liver erythroid progenitors. Furthermore, mice infected with recombinant retroviruses develop erythrocytosis and splenomegaly, demonstrating that these receptor isoforms support erythropoiesis in the adult animal.…”
Section: Discussionmentioning
confidence: 99%